Fixation of femoral neck fractures with three cannulated screws: biomechanical changes at critical fracture angles - Öner, Kerim; Paksoy, Ahmet Emre; Özer, Alaettin (Journal of Surgery and Medicine, 2020)
Aim: Increased fracture angle in the coronal plane results in more instability and complications in femoral neck fractures. Our aim in this study was to analyze biomechanical changes at critical fracture angles (30 degrees, 50 degrees, and 70 degrees) as described in Pauwels classification. Methods: A femur model was obtained by 3D computerized tomography (CT) scanning. The angle of femoral neck fracture in the coronal plane observed on the CT image was created on the model at 30, 50 and 70-degree angles. Three cannulated screws were placed in the inverted triangle position. Screws were named “anterior-superior” (A), “posterior -superior” (B), and “inferior” (C). The obtained three different models were transferred to the ANSYS Workbench program. Von Mises stress distribution on the screws and distal fracture surfaces were recorded. Results: In the 30-degree fracture model, the maximum stress was 18.062 MPa on the "A" screw. It was 22.13 MPa on screw "B" and 16.21 MPa on screw "C". In the 50-degree fracture model, the maximum stress values were 68.04 MPa, 89.52 MPa and 48.94 MPa in screws "A", "B", and "C", respectively. In the 70-degree fracture model, the maximum stress values were 120.02 MPa, 138.32 MPa and 98.37 MPa in screws "A", "B", and "C", respectively. The stress values on the distal fracture surfaces were 13.54 MPa, 43.80 MPa, and 50.07 MPa in the 30, 50, and 70-degree models, respectively. Conclusion: Increasing fracture angle from 30 to 50 degrees in femoral neck fractures significantly increases the stress on the distal fracture surface and implants. However, this increase is minimal at angles higher than 50 degrees.